2019
DOI: 10.4136/ambi-agua.2261
|View full text |Cite
|
Sign up to set email alerts
|

Potentially toxic metals in lotic systems with aptitude for aquaculture at the watershed Mantaro River, Peru

Abstract: The objective of the study was to analyze the concentration of Cu, Zn, Fe, Pb and As in river water suitable for aquaculture in the watershed of the Mantaro River using multivariate statistical methods, during the period 2011-2013. The determinations of total heavy metals in water collected during two different climatic periods were performed by atomic absorption spectrophotometry, according to the methodology recommended by FAO. The results obtained show that, in the seven rivers evaluated, the average concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(20 reference statements)
0
2
0
1
Order By: Relevance
“…It is evident that the hypotheses of authors such as Arce (2017) and Custodio et al (2019Custodio et al ( , 2020, who state that the mining liabilities located in the headwaters of the Mantaro basin are the cause of the metals present in the waters of the Mantaro River and the channels studied. Likewise, it is shown that the waters studied are predominantly alkaline, with pH values from 7.3 to 8.8, denoting a physicochemical similarity with the alkaline and polluted scenario of the Chachas River, described by Aylas et al (2021).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is evident that the hypotheses of authors such as Arce (2017) and Custodio et al (2019Custodio et al ( , 2020, who state that the mining liabilities located in the headwaters of the Mantaro basin are the cause of the metals present in the waters of the Mantaro River and the channels studied. Likewise, it is shown that the waters studied are predominantly alkaline, with pH values from 7.3 to 8.8, denoting a physicochemical similarity with the alkaline and polluted scenario of the Chachas River, described by Aylas et al (2021).…”
Section: Discussionmentioning
confidence: 96%
“…Undoubtedly, it is necessary to expand the investigations regarding heavy metals in the Mantaro river basin to correlate the geochemical dispersion in other matrices such as soils and sediments. [18][19][20][21][22]…”
Section: Discussionmentioning
confidence: 99%
“…References [ 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 ...…”
unclassified